A (diborole)cobalt complex with a C-H···B Bridge, CpCo(1,3-C3B2Me5H), and its thallium derivative: synthesis, structure, and bonding - Muratov, Dmitry V.; Siebert, Walter (European journal of inorganic chemistry, 2012)
The reaction of CpCo(1,3-C3B2Me5H) (1) with CpTl affords the thallium derivative CpCo(1,3-C3B2Me5)Tl (2). The structures of 1 and 2 were determined by X-ray diffraction at 100 K. An “extra” hydrogen atom in 1 occupies a C-H···B bridging position. According to DFT calculations, 1 exists as a mixture of two enantiomers with an enantiomerization barrier of only 0.5 kcal mol-1. The transition state has Cs symmetry with an endo-CH hydrogen atom. The isomeric iso-1with the Co-H···B bridge is less stable than 1 by 10 kcal mol-1.The formation of 1 and iso-1 from C3B2Me5H and CpCo(C2H4)2 have almost equal activation energies. The isomerization of iso-1 to 1 was shown to proceed as a two-step hydrogen transfer. The bonding of the “extra” hydrogen atom in the related CHB-bridged carborane nido-2,3,5-C3B3R5H2 and metallacarboranes M(C5R5)(C3B2R′5H) (R, R′ = H, Me; M = Co, Rh, Ir) as well as their hydridic isomers MH(C5R5)(C3B2R′5) was compared. According to energy decomposition analysis, the bonding of the parent anion [CpCo(1,3-C3B2H5)]- with metal cations becomes stronger in the following order: K+ < Na+ < Tl+ < Li+ < [RuCp]+. The attractive interactions between the [CpCo(1,3-C3B2H5)]- and Tl+ fragments are 68 % electrostatic and 32 % covalent.